The determination of heavy metals in leachate using inductive couple plasma mass spectroscopy (ICP-MS) - Mohd Razif, Rau’atul Jannah; Abdullah, Shakila; Khamidun, Mohd Hairul (Penerbit UTHM, 2020)
The heavy metal pollution normally caused by the open dumping of the municipal solid waste (MSW) which contains tons of different substances that are toxic and harmful that may adversely effect on the environmental health. In order to get closer to the leachates characteristic, 150 representatives MSW leachate samples were collected and analyzed from May to June 2017 from two different sampling points around Parit Raja, Johor. The analysis of the MSW leachates were included the pH, temperature, turbidity, color, Total Dissolved Solid (TDS), Total Organic Carbon (TOC), Total Suspended Solid (TSS), conductivity of heavy metals and radionuclides content in it. The result clearly shows that most of the MSW leachates characteristic has exceed the discharged limit assigned by the DOE and obviously shown the presences of heavy metals in it such as the Cd, As, Ni, Cr, Cu, Pb and U. All of the result obtained is then compared to the standard discharged limit set by the Department of Environment (DOE). This study generally focused on the determination of the heavy metals in the leachate using the Inductively Coupled Plasma Mass Spectroscopy (ICP-MS) and will be profit the environment to be safeguarded against elevated levels of the toxic materials.